Prevalência de Staphylococcus pseudintermedius resistente à meticilina (MRSP) em cães com piodermite atendidos no Hospital Veterinário da UFMG entre março e julho de 2013 - Larissa Silveira Botoni (2014)
Staphylococcus pseudintermedius is the most commonly isolated bacteria in dogs and is often associated with pyoderma and otitis in these animals. In the past years, methicillin resistant Staphylococcus pseudintermedius (MRSP) was described. These microorganisms have in there genome the mecA gene, responsible for the transcription of the PBP2a protein that reduces the susceptibility of these bacteria to all beta - lactamic antibiotics. The aim of this study was to evaluate the frequency of MRSP in dogs with superficial pyoderma presented at the Veterinary Hospital of UFMG. Forty-three dogs with superficial pyoderma were selected for the study diagnosed by physical and dermatological examination from march to July of 2013. From the selected animals, 75% had a history of prior antibiotic therapy. The samples were collected in sterile swab secretion of skin lesions and right nostril and were streaked on sheep blood agar and subsequently evaluated phenotypically and genotypically. At the phenotypic identification, 88 % of the isolates were classified as SIG (Staphylococcus pseudintermedius Group). At the genotypic identification for classification as Staphylococcus pseudintermedius, this number grows to 91 %, showing a significant correlation with the result of biochemical identification. A significant correlation between the species identified in skin lesions and nostrils. In the antibiogram, prevalence of resistance was amikacin 7% to 23% amoxicillin + clavulanate , 24% cephalexin , chloramphenicol 18% , 38% enrofloxacin 40% streptomycin , gentamicin 30% , 34% oxacillin, 77% penicillin , polymyxin B 6% , 62% and 77% tetracycline trimethoprim sulfa . Thirty-five percent of the samples had the mecA gene, demonstrating a significant correlation with the prevalence of oxacillin resistance. We also observed a significant correlation between the frequency of mecA in the lesions and nostrils. There was no correlation between previous antibiotic therapy and frequency of mecA gene in samples. In conclusion, S. pseudintermedius is the most common bacteria in canine pyoderma and the mecA gene is present in significant frequency in the lesions and nostrils of the tested animals.